2021
DOI: 10.1155/2021/8849066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Rail Transit Network on Residential and Commercial Land Values in China: A Complex Network Perspective

Abstract: Urban rail transit can improve a city’s accessibility. However, high construction and operation costs restrict the development of urban rail transit. Value capture recoups the additional value that the investments of urban rail transit confer to local land and is considered to be an effective measure to alleviate this financial problem. Understanding the land value uplift effects of urban rail transit is essential for understanding value capture. This study applied a Space-P model of urban rail transit network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Their results showed that high degree and low closeness centrality in the road network is correlated with improved ride-sharing accessibility, while betweenness centrality has no significant impact. Wen et al (2021) used network size and commonly used complex network metrics of average path length, and average clustering coefficient to identify the relationship between land value and topological properties of urban rail transit. The authors reported that land price is positively correlated with the number of nodes and the average clustering coefficient and negatively correlated with the average path length.…”
Section: Complex Network Approachesmentioning
confidence: 99%
“…Their results showed that high degree and low closeness centrality in the road network is correlated with improved ride-sharing accessibility, while betweenness centrality has no significant impact. Wen et al (2021) used network size and commonly used complex network metrics of average path length, and average clustering coefficient to identify the relationship between land value and topological properties of urban rail transit. The authors reported that land price is positively correlated with the number of nodes and the average clustering coefficient and negatively correlated with the average path length.…”
Section: Complex Network Approachesmentioning
confidence: 99%
“…Urban rail transit experienced rapid development worldwide due to its advantages in reducing traffic congestion, greenhouse gas emissions and improving accessibility [1][2][3]. By the end of 2020, the total mileage of the urban rail transit (URT) in the world reached 33,346 km, and the total mileage in the mainland of China reached 7,970 km, ranking first worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…As an essential part of all urban traffic activities, the urban metro network plays a vital role in the sustainable development of modern cities [1][2][3]. The metro network system is a complex network composed of multiple nodes and edges, and its topology structure forms the cornerstone of how it functions [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%